Cell-specific proteome analyses of human bone marrow reveal molecular features of age-dependent functional decline - Hennrich, Marco; Horn, Patrick; Eckstein, Volker; Ye, Fei; Ding, Ximing; Poisa-Beiro, Laura; Luft, Thomas; Ho, Anthony Dick (Nature Communications, 2018)
Ageing causes an inability to replace damaged tissue. Here, the authors perform proteomics analyses of human haematopoietic stem cells and other cells in the bone marrow niche at different ages and show changes in central carbon metabolism, reduced bone marrow niche function, and enhanced myeloid differentiation.
Gesehen am 31.10.2018